Bank credit, public financial incentives, tax financial incentives and export performance during the global financial crisis. (1st October 2019) - Okafor, Luke Emeka; Bhattacharya, Mita; Apergis, Nicholas
Abstract: This paper investigates the extent to which access to credit, public financial incentives and tax financial incentives affect export performance using the EU‐EFIGE/Bruegel‐Unicredit data set, covering firms within Austria, France, Germany, Italy, Spain, Hungary and the UK during the 2008 global financial crisis. The results show that firms receiving credit or benefiting from public financial incentives display higher export intensity and export a greater number of product lines compared to those that did not, especially in countries with better access to credit and/or financial incentives during the crisis. Further, firms benefiting from tax financial incentives show a better export performance compared to those that did not, regardless of the degree of access to credit and/or financial incentives in the country in which they operate. In addition, the effect of access to credit and public finance incentives on export performance is found to be size‐dependent, while the effect of tax financial incentives is not. We suggest that governments should promote publicly funded financial incentives along with conventional schemes, such as R&D subsidies, to promote exports, particularly during a period of financial crisis.